A plasma electron source for generating beam plasma at low gas pressures. (September 2017) - Xu, Jianping; Tian, Xiubo; Gong, Chunzhi; Li, Chunwei; Wu, Mingzhong; Wang, Jiajie; Ma, Tianhui
Abstract: A plasma electron source design for generating beam plasma at low gas pressures is reported. The designed plasma electron source can run stably in the pressure range between 0.1 Pa and 4 Pa. The electron source emission current increases as the working pressure increases. The DC electron beam can reach 11 A at an extraction voltage of 400 V and a gas pressure of 4.0 Pa, which is experimentally verified in this article. This low energy and high current electron beam interacts with gas molecules to generate a beam plasma, which increased the plasma electron source output current. As the working pressure and emission current increased, the beam plasma emission spectrum intensity increased. Highlights: A high current plasma electron source was designed and used to treat insulating components at low pressure. The beam plasma emission spectrum intensity increased with working pressure and emission current. The beam plasma increases the electron source emission current.